Sistema produtivo agrário brasileiro consumidor de agrotóxicos como fonte de violência - Dunck, Ellen A. Fernandes Magni (2016)
The incident of aerial spraying of pesticides occurred in May of 2013 on the Municipal Rural School São José do Pontal, within the rural settlement Pontal dos Buritis located 130 km from Rio Verde - Goiás, where more than 100 children and adults were Intoxicated, was the inspiration for this research. The objective is to study the Brazilian agricultural production system from 1960, coinciding with the "green revolution". Developed after World War II by large corporations, the study of the "green revolution" showed that it was more of a violent policy than a peaceful solution to eradicate hunger and increase and improve food productivity as it preached. This new rationality based on the homogeneity of the production brought about by the "green revolution", its science and its politics, made possible the development of the Agroindustrial Complexes, favoring the hegemonic power. The "green revolution" was rather a technical-scientific package that would impose the mechanization of crops and the massive use of highly toxic chemical substances - agrochemicals, generating ever more ecological and social scarcity and violence.